Akreditasi Sekolah dan Peningkatan Mutu Pendidikan - Islamiya, Izzatul; Noor, Triana Rosalina (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This study aims to describe the efforts to improve the quality of education based on school accreditation at SMP Tamaddun Afkar Sidoarjo. This research is a qualitative case study utilizing interview, observation, and documents as data sources, and is analyzed descriptively. The purposively selected research subjects include the Principal, Curriculum Head, Facilities Head, Administration Head, and Grade VII Teachers. The results of this study indicate that efforts to improve education quality are based on graduate competency standards, content standards, process standards, assessment standards, educator and education personnel standards, facilities and infrastructure standards, management standards, and financing standards. These efforts are realized through the establishment of five flagship programs for graduate competency standards, preparation of lessons and curricula according to National Education Standards for content standards, and structured planning, implementation, and evaluation of learning for process standards. For assessment standards, minimal achievement criteria are set to align with learning objectives to support graduation and class promotion decisions. Personnel competency standards are enhanced through increased self-development activities. Facilities and infrastructure standards are addressed by procuring representative facilities, while financing standards involve allocating incoming and outgoing funds for operational costs and inventory according to their intended useless needs.